Tourist Attraction, Image, and Memorable Experience On Revisit Intention: Evidence From Bonjeruk Tourism Village - Lalu Trisna Sakti; Titien Damayanti; Luh Yusni Wiarti (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Lombok Island has become a popular destination for domestic and international tourists due to its natural and cultural richness. Despite the growth of Bonjeruk Tourism Village, challenges remain in sustaining tourist loyalty. This study examines the influence of Tourist Attraction and image on revisit intention, mediated by memorable tourism experiences. A total of 110 tourists who had visited Bonjeruk Tourism Village were surveyed using literature review, interviews, and questionnaires. Data were analyzed through a quantitative approach with SEM-PLS using SmartPLS 3.0. The findings reveal that Tourist Attraction significantly affects memorable tourism experiences but does not directly influence revisit intention. Conversely, destination image exerts both direct and indirect positive effects on revisit intention through memorable tourism experiences. Moreover, memorable tourism experience mediates the relationships between both Tourist Attraction and image with revisit intention. These results provide practical insights for destination managers to enhance Tourist Attraction and image by integrating memorable experiences to strengthen tourist revisit loyalty.